Christiano Stocker das Neves: A Polemical Actuation - Sampaio, Maria Ruth Amaral de (Revista do Instituto de Estudos Brasileiros, 1995)
The architet Christiano Stockler das Neves since the 1910´s has participated with his father in the urban development of São Paulo. He had an important role in the process of verticalization of the city and in the introduction of new building techniques. The influence received from the École des beaux Arts through the University of Pennsylvania, where he got his architectural degree, was fundamental for his constant search for beauty, the respect of tradition and his critics of modern architecture. Founder of the architecture deparment ar the Mackenzie Engineering School in 1917, and first director until 1957, taking active in the formation of 40 classes of architects. In 1929 he was on of the initiators of IPA, Paulista Institute of Architects.